PsycEXTRA Dataset 2008
DOI: 10.1037/e722352011-097
|View full text |Cite
|
Sign up to set email alerts
|

When Healthy Food Makes You Hungry

Abstract: Do subtle cues for imposed healthy eating make consumers hungry? Imposed healthy eating signals that the health goal was sufficiently met, and thus it increases the strength of the conflicting motive to fulfill one's appetite. Accordingly, consumers asked to sample an item framed as healthy later reported being hungrier and consumed more food than those who sampled the same item framed as tasty or those who did not eat at all. These effects of healthy eating depend on the consumer's perception that healthy eat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…These studies showed that ad libitum intake can be made comparable to fixed intake if the serving is increased sufficiently; however, serving different portion sizes may confound the interpretation of other outcomes. Examples of cognitive factors that may influence the comparison between fixed and ad libitum intakes are perceptions of the food and the motivations for eating it (Finkelstein & Fishbach, 2010). In the present study, requiring the consumption of a fixed amount led to decreased hunger ratings and reduced meal energy intakes compared to ad libitum intake; these differences were consistent with the differences in the amount of salad consumed, but the contribution of motivational factors cannot be independently evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that ad libitum intake can be made comparable to fixed intake if the serving is increased sufficiently; however, serving different portion sizes may confound the interpretation of other outcomes. Examples of cognitive factors that may influence the comparison between fixed and ad libitum intakes are perceptions of the food and the motivations for eating it (Finkelstein & Fishbach, 2010). In the present study, requiring the consumption of a fixed amount led to decreased hunger ratings and reduced meal energy intakes compared to ad libitum intake; these differences were consistent with the differences in the amount of salad consumed, but the contribution of motivational factors cannot be independently evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, few studies have compared the effects of meal manipulations using fixed versus ad libitum consumption. Although using fixed amounts of food reduces variability in intake, imposed consumption differs from typical eating conditions and may have consequences due to differences in demand characteristics or motivational factors (Rolls & McDermott, 1991; Finkelstein & Fishbach, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Useful insights emerge from consumer research (Finkelstein and Fishbach 2010;Irmack, Vallen and Robinson, 2011). Features such as the perceived variety of a food assortment (Kahn and Wansink 2004), and the size of plates, serving bowls, and/or utensils can all impact the quantity that will be consumed.…”
Section: Creating a Healthy Home Environmentmentioning
confidence: 99%
“…First, when food is described as healthy, people have been shown to rate it as less tasty and report enjoying it less (Raghunathan et al, 2006). Second, the mere presence of a healthy option on a menu can lead individuals to believe they have fulfilled their health goal (referred to as a “health halo effect;” Wilcox, Vallen, Block, & Fitzsimons, 2009), which itself can lead to goal violations by making that goal less accessible (Finkelstein & Fishbach, 2010). Believing that the health goal has been fulfilled can also lead to individuals feeling ‘licensed’ to indulge (Chiou, Yang, & Wan, 2011; see also Wilde, 1982).…”
mentioning
confidence: 99%
“…By not explicitly drawing attention to the healthfulness of a food, subtle health messages, such as healthy images rather than words, might avoid several of the pitfalls associated with explicit messages. First, a more subtle health message may not cause people to believe they have fulfilled their health goal, so they may not feel licensed to indulge, and the health goal would remain accessible (Finkelstein & Fishbach, 2010). Second, a subtle health message may be less likely to be perceived as a command to behave in a certain way and therefore be less likely to cause reactance.…”
mentioning
confidence: 99%